LITERATURE STUDY: THE EFFECTIVENESS OF GUIDED DISCOVERY ON THE STUDENT COMPETENCY IN SCIENCE EDUCATION - Puja Ramadhani; Lufri Lufri (Department of Science Education, 2021)
This analysis is motivated by the large number of studies on the result of guided discovery (GDL) in relation to the research competencies with respect to students, especially in learning science (Natural Sciences). Based on the research article obtained that the low competency of students can be pursued by applying a learning design that requires students to be active during the research process. GDL is one of the interactive research models which encourages students to be central in the research process. GDL is effective to encourage the activeness of students in the research course, because this research model requires students to play an active part in conclusion their own knowledge with the guidance of the teacher. The view of that analysis was to look at the efficiency of the influence of GDL on the student competencies in science. That investigation is an expost facto study with descriptive data analysis. Based on the results of the investigation, the article found which the influence of guided discovery has a direct reaction on the competence of students in learning science